2021
DOI: 10.1111/ger.12554
|View full text |Cite
|
Sign up to set email alerts
|

Number of teeth, denture wearing and cognitive function in relation to nutritional status in residents of nursing homes

Abstract: Background Although statistical associations between tooth loss and cognitive decline have been reported, there are few previous studies on denture wearing. Additionally, it remains unclear whether nutritional status mediates this association. Objective Our purpose was to test for the hypothesis that the association between the number of teeth and denture wearing with cognitive function is mediated by nutritional status in residents of nursing homes. Materials and Methods We enrolled 162 participants who requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Our study is in accordance with the previous study where emotional wellbeing was indirectly affected by dental health & prosthetic rehabilitation through nutritional status. 31 They had experienced depression, nervousness, restlessness & lack of interest towards their daily life during COVID-19 pandemic. Specifically, loneliness was associated with higher levels of depression for older adults who were living in old age home during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study is in accordance with the previous study where emotional wellbeing was indirectly affected by dental health & prosthetic rehabilitation through nutritional status. 31 They had experienced depression, nervousness, restlessness & lack of interest towards their daily life during COVID-19 pandemic. Specifically, loneliness was associated with higher levels of depression for older adults who were living in old age home during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased intake of essential nutrients has been reported to be a risk factor for decline in cognitive skills and memory loss. 31 Complete edentulousness may not be life threatening and yet it has been shown to have a negative effect on the quality of life of older adults. 43,44 This study is concurrent with a previous study that has demonstrated the association between edentulism, malnutrition and poor emotional wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…Examiners also determined the number of teeth and removable denture use. Based on this information, dentition status was divided into three categories (≥20 teeth, ≤19 teeth with removable dentures, and ≤ 19 teeth without removable dentures) 27,28 . Furthermore, the number of pairs of opposing natural teeth excluding third molars, termed functional natural tooth units (FNTUs; range 0–14), was counted.…”
Section: Methodsmentioning
confidence: 99%
“…Based on this information, dentition status was divided into three categories (≥20 teeth, ≤19 teeth with removable dentures, and ≤ 19 teeth without removable dentures). 27,28 Furthermore, the number of pairs of opposing natural teeth excluding third molars, termed functional natural tooth units (FNTUs; range 0-14), was counted. To assess occlusal status, it is more common to use pairs of opposing natural or prosthetic teeth, termed functional tooth units (FTUs).…”
Section: Oral Examinationsmentioning
confidence: 99%
“…The deterioration of cognitive functions, behavioral disturbances, and inadequate nursing and parasanitary training contribute to poor oral health in elderly people with dementia [ 18 , 19 , 20 ]. Studies show that frail people having fewer teeth are associated with a lack of nutritional supply and that dental status could play a role in musculoskeletal frailty [ 6 , 21 ] and cognitive impairment [ 22 ]; additionally, the presence of lesions of the oral mucosa could interfere with the nutrition of elderly patients [ 6 , 23 , 24 , 25 ]. The first alarm bell is the lack of energy that the elderly manifest during the day and that social health workers notice and report to the doctor in order to act preventively/promptly on potentially reversible causes [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%